SONG KEPLEK: OKUPASI INTENSIF MANUSIA PADA PERIODE PASCA-PLESTOSEN DI GUNUNG SEWU - Retno Handini; Harry Widianto (BRIN, 1998)
Song Keplek is a cave located in the Southern Mountains of Java, which is traditionally known as Gunung Sewu. This area that extends from west (Wonosari) to east (Pacitan) has its own distinctive morphological landscape, which is characterized by sinoid-shaped karst hills. On one of these hilly slopes - which is administratively included in the area of Pagersari Village, Punung District, Pacitan Regency - Song Keplek is located, about 300 meters southwest of the Wonogiri - Pacitan highway.